Prediction of testosterone deficiency using different screening indexes in adult American men: An NHANES cross-sectional study - Bo Zhang; Yi Gu; Yuanyuan Li; Xingliang Feng (PLoS ONE, 2025)
Background Testosterone levels are closely associated with visceral obesity, insulin resistance, and lipid metabolism. The objective of this study was to investigate the associations among eight indicators related to visceral obesity, insulin resistance, lipid metabolism, and testosterone levels. Methods The data were obtained from a cross-sectional survey based on National Health and Nutrition Examination Survey (NHANES) 2013–2016. Logistic and linear regression were employed to assess the associations between these inicators and testosterone levels. Simultaneously, the receiver operating characteristic (ROC) curve was utilized to evaluate their predictive capacity for testosterone deficiency (TD). Results Data from a collective of 1514 individuals selected from NHANES were analyzed. After adjusting all potential confounders, a tight association was identified between these eight indexes and TD. The ROC curve analysis showed that the triglyceride-glucose waist-to-height ratio (TyG-WHtR)is the best predictor of testosterone deficiency (AUC: 0.7760, 95%CI: 0.7460–0.8060), with a cut-off value of 5.375. Further analyses indicated that participants with higher TyG-WHtR index exhibitrd a lower total testosterone level(β: −79.36,95%CI: −105.90, −52.82). Additionally, males in TyG-WHtR index tertile 3 had a higher risk of TD (OR: 6.61, 95%CI: 2.90,15.07), and lower total testosterone levels (β: −121.9, 95%CI: −186.82, −56.98). All the results remained stable in the subgroup analyses stratified by diabetes and hypertension. Conclusions We found that these indexses are tightly associated with testosterone levels in U.S. adult men. Moreover, the TyG-WHtR index demonstrates the most effective predictive performance in the population. However, more well-designed studies are still needed to validate their association.